Pentingnya Pendidikan Agama Kristen untuk Membangun Toleransi pada Masyarakat Majemuk - Ferdi Eka Darma; Walde Mesah; Semuel Linggi Topayaung (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2024)
Christian Religious Education (PAK) plays a crucial role in strengthening the value of tolerance among Indonesian society which is very diverse in cultural, religious, tribal and ethnic aspects. In the context of a pluralistic society, PAK aims to instill the values ​​of love, forgiveness, respect and empathy in accordance with Christian teachings. These values ​​are the basis for harmonious interaction between individuals from various backgrounds. This article discusses how PAK can be a means of increasing understanding of inter-religious tolerance through inclusive education that respects diversity. Through the PAK learning process, Christians are taught to respect differences without viewing other religions or cultures as threats. On the contrary, these differences are considered as wealth that deserves respect. PAK also plays a role in creating inclusive character, which helps students to practice love and respect for others, as taught by Jesus in the message 'love your neighbor as yourself. ' In this context, interreligious dialogue is strongly encouraged as a preventive measure against conflict and to strengthen unity amidst diversity. PAK teachers, with full responsibility, are tasked with guiding students so that they are able to live in harmony with various groups, without being influenced by differences. It is hoped that PAK's contribution will be able to create a society that is harmonious, harmonious and far from conflict, thus making Indonesia a model of a pluralistic society full of tolerance and unity.